Clinical Application of the Musculoperiosteal Iliac Flap for Osteonecrosis of the Femoral Head. Issue 6 (December 2021) - Li, Bo-Rui; Qin, Kai-Rong; Liu, Bao-Yi; Wang, Ben-Jie; Qiu, Xing; Li, Zhi-Gang; Lineaweaver, William C.; Zhang, Feng; Zhao, Dewei
Abstract : Background: Osteonecrosis of the femoral head (ONFH) often affects young, active patients, and the femoral head's preservation is the primary goal of treatment for this disease. Vascularized iliac crest bone grafting is one of the many vascularized procedures used in treating ONHF. In some cases, we selectively performed this procedure using the musculoperiosteal iliac flap with the ascending branch of the lateral femoral circumflex artery for ONFH treatment. Methods: Twelve patients (12 hips) with nontraumatic femoral head necrosis underwent musculoperiosteal iliac flap transfer with the ascending branch of the lateral femoral circumflex artery. The Harris Hip Score (HHS), visual analog scale score, and double-hip X-ray findings were used to analyze hip function changes within 10 days preoperatively and 6 and 12 months postoperatively. Results: The mean HHS increased from 52.33 ± 3.34 preoperatively to 65.92 ± 5.04 6 months postoperatively and 79.75 ± 3.84 12 months postoperatively, and the data showed a statistical significance difference between preoperative and postoperative (F = 131.90, P < 0.01). The HHS at 6 and 12 months after surgery were significantly different ( P < 0.01). The visual analog scale score showed the same trend. The x-ray of hip joints at 6 and 12 months after surgery showed that the femoral heads' shape and contour were good, femoral heads did not collapse, and the transferred bone flaps healed well. Conclusions: Musculoperiosteal iliac flap transfer with the ascending branch of the lateral femoral circumflex artery may be an effective method with a high clinical success rate for treating young patients with early to midstage ONFH.